HIGH-TUNING RANGE FERROFLUID-BASED SOLENOID INDUCTOR FOR WIRELESS LOCAL AREA NETWORK (WLAN) APPLICATIONS (Jurnal Teknologi (Sciences & Engineering), 2016)
In this work, a high-tuning range ferrofluid-based liquid solenoid inductor is proposed. This project utilized the light hydrocarbon-based ferrofluids (EMG 901 660mT type) with magnetic permeability of 5.4. The liquid is injected into the channel of the designed solenoid inductor to improve the tuning range and quality factor of the device. This is achieved by several tuning methods; by changing the number of turns, the thickness and width of copper coils, the cross-sectional area of ferrofluid across the channel and the self-resonance frequency (SRF). The proposed tuning solenoid inductor is simulated using a 3D full-wave electromagnetic field tool, ANSYS HFSS. The simulation is done by injecting the ferrofluid liquid into the channel by a step of 20% until it reached 100%. The inductance values are set to be tuned at a frequency of 2.45 GHz. The simulation results show the inductance values can be tuned from 4.5 nH to 15.2 nH with a maximum quality factor of 25. On the other hand, for tuning capability, the inductor is capable to be tuned with high tuning range of up to more than 200%.